Problematika Pembayaran Fidyah Puasa Melalui Aplikasi Kitabisa.com - Muthoharoh, Isnaini Lu'lu' Atim; Ichwayudi, Budi (FENOMENA, 2022)
The mechanism for payment fidyah through the Kitabisa.com application raises various problems, because the difference of opinion among scholars regarding the terms of fidyah payment and the diversity of nominal values ​​of each organizer on the Kitabisa.com application page is a complex matter to be studied more deeply. This research using descriptive qualitative method and phenomanological approach. Through this approach, will be find a meeting point that can build and renovate the application structure and the organizers. The findings in this study indicate that the effectiveness and superiority of the application do not cover all the shortcomings that surround it. Transition of payment fidyah originally with the type of food and the switch money cannot be justified unilaterally, because the previous scholars in making certain decisions through the process of ijtihad. Beside that, conflicts over nominal differences from various implementing agencies that seem to overlap from the unity of institutions can be adjusted periodically based on the validity of applicable Islamic law.